Some crack problems in engineering structures - Kok, Kheong Shiun. (2009)
The failure of engineering structure by cracking is always undesirable. It involves human lives that are put in jeopardy, economic losses and the interference with the availability of products and services. Therefore, an understanding of fracture mechanics is crucial for engineers in designing engineering structure especially those under high tensile stress.